Levantamiento geológico-estructural a escala 1:25000 de la Zona Sur de la parroquia Cazaderos, cantón Zapotillo y provincia de Loja. - Infante Requenes, José Yasmani (2023)
The structural geological survey scale 1:25000, carried out in the southern area of Cazaderos parish contains an extension of 59.04 km2, is located to the northwest of the Zapotillo canton, and the west of the Loja province, it is limited to the North by the area North of Cazaderos, to the South with Peru, to the East with the parish of Mangahurco and to the West with Peru. The geological-structural survey was carried out using the contact mapping method, which allowed the characterization of five lithological Units. Cazaderos Unit, Cañaveral Unit, Mangahurco Unit and Alluvial Deposit. In which the Cazaderos Unit constitutes the largest extension of the study area with 29.47 km2 of the total area, it presents alternations of siltstones, shales, interspersed with sandstone and limestone levels. The alluvial deposit covers an area of 5.34 km2, and is made up of sand, gravel, and rounded and sub-rounded pebbles from sedimentary and volcanic rocks. The Cañaveral Unit is visualized in anthropic outcrops, it is made up of lithic sandstones, micro conglomerates, conglomerates and in small dimensions shales and siltstones. The Mangahurco Unit is located to the SW and extends to the NE, covers an area of 7.40 km2 of the study area, formed in the Late Cretaceous period, rests concordantly on the Fm. Tronco Quemado, and below lies discordantly to the Fm. Cañaveral, where alternating siltstones and shales can be seen, with levels of sandstone and scarcely micro conglomerates. Structurally, the study area is marked by folds, inferred and observed faults, product of the tectonic efforts to which the earth's crust is exposed. Inferred folds have been evidenced throughout the study area, specifically in the Cazaderos Unit, to the SW there is an anticlinal fold observed in a NE-SW direction, in the same Unit there is an inferred fold located to the NW of the studied area in a NE direction -SW. Through photo interpretation, 8 faults were inferred: two normal faults that are found along the work area with a NW-SE and NE-SW direction and six inferred faults: four with a NW-SE direction and two with a NE direction. -SW. Key words: Structural geology, contact mappingm, geological survey.